Analysis of Hand-Eye Coordination, Leg Strength, and Self-Confidence on High School Students' Volleyball Underhand Passing - Yuyung Afrilia; Muh. Adnan Hudain; Irvan Irvan (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
This research is driven by the need to identify the specific physical and psychological factors that influence the underhand passing performance of extracurricular volleyball students at High School 8 Bulukumba. The primary objective is to analyze the impact of hand-eye coordination, leg muscle strength, and self-confidence on this fundamental skill. Employing a quantitative methodology, the study utilized a purposive sampling technique to select 20 participants. Data were gathered through structured physical assessments and psychological questionnaires, then analyzed using multiple regression and t-tests. The empirical results indicate that all three variables significantly affect performance, both partially and simultaneously. Hand-eye coordination contributes 86% to passing ability (t = 2.304, p = 0.035), while leg muscle strength contributes 89.2% (t = 2.792, p = 0.013) as a vital foundation for body stability. Notably, self-confidence emerged as the most dominant factor, contributing 90% (t = 4.252, p = 0.001), confirming that psychological maturity is directly proportional to technical accuracy. Collectively, these three variables account for 96.1% of the variance in underhand passing skills. These findings offer a strategic framework for coaches to integrate mental fortitude with physical conditioning to effectively enhance the technical proficiency and competitive readiness of student-athletes.